2004
DOI: 10.1002/jcb.20080
|View full text |Cite
|
Sign up to set email alerts
|

Blocking anti‐apoptosis as a strategy for cancer chemotherapy: NF‐κB as a target

Abstract: Critical processes underlying cancers must be better understood to develop strategies for treatment and prevention. A chemotherapeutic strategy is proposed that is based upon re-establishment, with a drug, of nullified programmed cell death (apoptosis) in cancer cells, which to survive have mutated to block apoptosis. A chemotherapy that is specific against tumors implanted in mice demonstrated the feasibility of this principle. This therapy is specific because it affects a process unique to cancer cells. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 35 publications
1
49
0
4
Order By: Relevance
“…16,[22][23][24] These studies suggest that sensitization of cancer cells to apoptosis by inhibiting NF-κB activation may be a promising strategy for cancer treatment. [25][26][27][28] In early work, we and others 29 have shown that H 2 O 2 induces apoptosis in primary hepatocyte culture, but the rat HCC cell line ARL-6, which exhibits constitutive activation of NF-κB, appeared relatively refractory to this type of cell death. 30 We therefore considered that NF-κB may protect HCC cells from cell death induced by oxidative stress.…”
Section: Introductionmentioning
confidence: 94%
“…16,[22][23][24] These studies suggest that sensitization of cancer cells to apoptosis by inhibiting NF-κB activation may be a promising strategy for cancer treatment. [25][26][27][28] In early work, we and others 29 have shown that H 2 O 2 induces apoptosis in primary hepatocyte culture, but the rat HCC cell line ARL-6, which exhibits constitutive activation of NF-κB, appeared relatively refractory to this type of cell death. 30 We therefore considered that NF-κB may protect HCC cells from cell death induced by oxidative stress.…”
Section: Introductionmentioning
confidence: 94%
“…The pivotal role of the IKKβ/NF-κB signaling pathway in inhibition of PCD, tumor promotion, and tumor progression, together with the occurrence of constitutively activated NF-κB in various solid and hematopoietic malignancies, strongly suggests that IKKβ and/or NF-κB inhibitors would be useful in cancer therapy. In fact, much effort is currently invested in developing various IKKβ and/or NF-κB inhibitors and testing their efficacy in both animal models and human cancer (109,110). Many inhibitors currently available are not specific for either IKKβ or NF-κB.…”
Section: Ikk/nf-κb and Cancer Ikk/nf-κb Links Inflammation To Cancermentioning
confidence: 99%
“…The pivotal role of the NF-B signaling pathway in apoptosis, tumor promotion and tumor maintenance, strongly suggests that NF-B inhibitors would be useful in cancer therapy, and much efforts is currently invested in developing NF-B inhibitors in cancers (10,14,85,86). Several agents have been implemented to inhibit IKK/NF-B activity, because of the relevance of this process in cancer and those related with inflammation, such as curcumin, ginseng extract, resveratrol, green tea extract have anti-inflammatory and antiproliferative propertiese (87).…”
Section: Nf-b Inhibition: Strategy For Colorectal Cancer Therapymentioning
confidence: 99%